Letter : Aid for Spanish seamen - Marchbank, John
025a-0032-001 TELEGRAMS "BEWARE. NORWEST. LONDON." Telephone EUSTON 4771 (5 Lines) The National Union of Railwaymen. J. MARCHBANK General Secretary G. W. BROWN. Assistant General Secretary Head Offices Unity House, Euston Road, LONDON, N.W.1 Your Ref WMC/HVT/FC/620 In Your Reply Refer to F.M.A.2. 24th July, 1940. Sir Walter Citrine, General Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. Sir, Aid for Spanish Seamen. Further to my letter of the 17th instant, I have pleasure in enclosing a cheque for £500 in connection with the above. Yours faithfully, J Marchbank 292/946/25a/32